Pronouns in the Workplace: Developing Sociotechnical Systems for Digitally Mediated Gender Expression - Ale-Ebrahim, Ben; Gohring, Tristan; Fetterolf, Elizabeth; Gray, Mary L. (Proceedings of the ACM on Human-Computer Interaction, 2023)
Sharing personal pronouns (such as they/them, she/her, or he/him) in the workplace helps colleagues respectfully address each other. Many companies currently seek to design and implement new software tools to facilitate pronoun-sharing among employees. This paper analyzes the social processes of communication about pronouns in the workplace and identifies best practices for creating and using workplace pronoun-sharing software. We conducted 78 semi-structured qualitative interviews with various stakeholders involved in the launch of pronoun-sharing tools in workplace collaboration software, including transgender and queer people, HR and IT professionals, and LGBTQ advocacy organizations. We used an anthropological approach to qualitatively analyze interview materials and notes from interactions with research participants. We find that sharing personal pronouns is an ongoing communication process rather than a single act of information provision. Pronoun sharing tools encapsulate the tension between dynamic social processes of self-expression and technical systems of classification and information retrieval. People communicate their pronouns differently as they navigate identity expression across social contexts. Sharing pronouns is therefore both an individual expression of self-presentation and a complex act of social communication. Developers must create new methods for building pronoun-sharing tools that equip people to control ongoing social processes of self-expression instead of using an information retrieval approach that treats pronouns merely as stable, unchanging data.